DEVELOPMENT OF HOTS-BASED ASSESSMENT INSTRUMENTS (HIGHER ORDER THINKING SKILLS) FOR MARKET ECONOMICS SUBJECTS AND THE FORMATION OF CLASS X MARKET PRICES IN MAN 2 MADIUN CITY - Binti Munafi'ah; Siswandari; Sudarno (SOSIOEDUKASI, 2025)
This research aims to develop and validate a Higher Order Thinking Skills (HOTS)-based assessment instrument for Chemistry learning at MAN 2 Kota Madiun. The study adopts a Research and Development (R&D) approach using the Borg and Gall model, which involves stages of needs analysis, product design, expert validation, limited trials, wider implementation, and revision. The assessment instrument was designed to align with the core competencies and learning objectives of chemistry subjects while emphasizing problem-solving, analysis, and evaluation skills. Validation was carried out by experts in education, measurement, and chemistry, followed by trials with students to test reliability, validity, practicality, and effectiveness. The results showed that the developed HOTS-based assessment instrument met very valid criteria in terms of content, construct, and language. The instrument demonstrated high reliability and was considered practical by both teachers and students. Furthermore, its implementation indicated positive impacts on students’ engagement and their ability to think critically and analytically in solving chemistry problems. In conclusion, the HOTS-based assessment instrument for Chemistry is proven to be valid, reliable, practical, and effective in measuring higher order thinking skills. This study highlights the potential of integrating HOTS-oriented evaluation tools into classroom practice to foster critical and creative thinking among students, thereby supporting the improvement of learning quality in line with 21st-century educational goals.